Field measurement and influence mechanism analysis of the albedo for a typical urban concrete surface. Issue 6 (July 2019) - Xu, Kuo; Long, Enshen; Li, Jin; Xu, Luting
There has been an increase in impervious surfaces due to urbanization, which has led to a general decline in the albedo and an increase in radiative heat gain, thereby intensifying the urban heat island effect. Albedos of the urban underlying surfaces have a significant influence on the urban microclimate and building environment, but relevant studies have been inadequate. Field measurements were conducted on the temporal variation of the albedo by targeting on the common concrete roof, in variable weather conditions, such as during cloudy, sunny and rainy days. Five potential influencing factors were analysed by Pearson correlation, which showed a significant correlation of the surface albedo conditions with the solar altitude angle, diffusive solar radiation, diffusive radiation ratio and relative temperature. A fitting formula for the albedo conditions was developed by applying the multivariable regression method, and this was verified by experimental data. The results showed that the weighted average albedo of the concrete surface was 0.240 during the field measurement, but albedo values of similar surfaces presented in former studies varied from 0.110 to 0.406. The fitting formula (fitting R 2 of 0.807) allows an accurate interpretation on the impact rule of multiple factors on the albedo.